Investigating project issue factors as causes of construction contract terminations: the case of Ghana - Coleman, Charles .E; M. Mwanaumo , Erastus; Muya, Mundia; A. Rahman, Rahimi. (International Journal of Engineering and Technology, 2025)
This study aims to investigate and analyse the project issue factors (PIF) contributing to construction contract terminations within Ghana's construction industry. By identifying and understanding these key factors, the study seeks to provide valuable insights for stakeholders to improve project success rates, minimise disruptions, and foster sustainable growth in the sector. The research adopted a quantitative research approach, utilising techniques such as exploratory factor analysis (EFA) and structural equation modelling (SEM) to analyse data collected from 315 construction industry professionals in Ghana. A combination of purposive and random sampling techniques was employed to ensure a diverse and representative sample, considering participants' qualifications, experience, specialisations, and employment sectors. The study's findings revealed significant project issue factors (PIF) that contribute to construction contract terminations in Ghana. Top-ranking factors include contractor refusal to work with engineer instructions, construction time delays, failure to remedy defective works, and unsuitable materials on structures. The study underscores the importance of addressing these factors through enhanced communication, robust project management practices, quality control measures, and continuous professional development. The study’s methodology and comprehensive analysis add value to the literature as it contributes to the existing body of knowledge by focusing specifically on the Ghana’s construction industry and providing empirical insights into the factors driving construction contract terminations. The recommendations have practical implications for industry stakeholders, policymakers, and professionals, guiding them in implementing strategies to mitigate project issue factors (PIF) and improve overall project outcomes, thereby fostering a conducive environment for sustainable growth in Ghana’s construction industry.